2022
DOI: 10.1039/d1fo02758a
|View full text |Cite
|
Sign up to set email alerts
|

Ergothioneine exhibits longevity-extension effect in Drosophila melanogaster via regulation of cholinergic neurotransmission, tyrosine metabolism, and fatty acid oxidation

Abstract: Many studies have demonstrated the protective effect of ergothioneine (EGT), the unique sulfur-containing antioxidant in mushrooms, on several aging-related diseases. Nevertheless, to date, no single study has explored the potential...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…One of the components of the mushroom extracts is ergothioneine (ET), which is known for its effect on lifespan extension [ 75 , 76 ]. It should be noted that, in our extracts, ET concentration was about 0.1% (1.31 mg/g and 0.99 mg/g in the extracts of H. erinaceus and G. frondosa , respectively).…”
Section: Discussionmentioning
confidence: 99%
“…One of the components of the mushroom extracts is ergothioneine (ET), which is known for its effect on lifespan extension [ 75 , 76 ]. It should be noted that, in our extracts, ET concentration was about 0.1% (1.31 mg/g and 0.99 mg/g in the extracts of H. erinaceus and G. frondosa , respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, OCTN-1 has a higher expression level in the mitochondria, implying that EGT plays a significant role in mitochondria. As shown in Figure 2 , EGT can regulate NOXs [ 82 , 83 ], NADH oxidase [ 31 , 80 , 84 ], and GSH-Px [ 84 ]. Therefore, we inferred that OCTN-1 specifically transports EGT into the mitochondria to remove generated intracellular ROS and alleviate the aging process.…”
Section: The Biological Effect Of Ergothioneinementioning
confidence: 99%
“…Increase in GSH results in a corresponding increase in the ratio of GSH/GSSG [ 31 ]. Pan et al [ 83 ] confirmed that EGT can maintain the ratio of GSH/GSSG and increase lifespan in Drosophila .…”
Section: The Biological Effect Of Ergothioneinementioning
confidence: 99%
“…The regression equation of 12 phytohormones were obtained by plotting the detected peak areas of their corresponding concentrations (Supplementary Table 1). Meanwhile, the 100 mg of similar samples were also collected to, respectively, investigate the concentration of total sugar, soluble sugar, trehalose, and sucrose content using Sugar Content Assay Kit (Solarbio, Beijing, China) as described by Pan et al (2022). Three biological replicates of each sample were performed to estimate these plants physiological index.…”
Section: Extraction and Detection Of Phytohormones And Sugar Substancesmentioning
confidence: 99%